Mothers’ labor supply and conditional cash transfers: Evidence from Chile - Dona, Gonzalo (Estudios de Economía, 2023)
Taking advantage of a reform that made Chile’s most popular conditional cash transfer program substantially more generous, I study its impact on mothers’ labor supply using a difference-in-difference strategy. Previous research has focused on these effects near the inauguration of CCTs, never before more than 20 years later. I find that older mothers respond to the reform by increasing their probability of working, but young mothers between 18 and 24 years old reduce their labor force participation. Meanwhile, intensive margin responses are always non-positive. This is policy-relevant information to many countries with CCTs today.